Criminal liability for (self)-liberation of a person legally deprived of liberty under German, Swiss, Austrian, and the principality of Liechtenstein’s law (Ius Novum, 2023)
The subject of the article is regulations concerning the escape of a person legally deprived of liberty, that are in force in countries that have a Germanic legal tradition. The analysis of German, Swiss, Austrian and the Principality of Liechtenstein’s law is conducted against a background of Polish solutions. The aim of the study is to present similarities and differences between the solutions adopted in particular German-speaking countries, as well as between these solutions and the regulations contained in the Polish Penal Code.
Keywords: offence of liberation (and self-liberation) of a person deprived of liberty; offence of facilitating escape of a person deprived of liberty; offence of instigating to escape